2016
DOI: 10.1148/radiol.2016152110
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Radiomics Signatures for Predicting the Risk of Breast Cancer Recurrence as Given by Research Versions of MammaPrint, Oncotype DX, and PAM50 Gene Assays

Abstract: Purpose To investigate relationships between computer-extracted breast magnetic resonance (MR) imaging phenotypes with multigene assays of MammaPrint, Oncotype DX, and PAM50 to assess the role of radiomics in evaluating the risk of breast cancer recurrence. Materials and Methods Analysis was conducted on an institutional review board–approved retrospective data set of 84 deidentified, multi-institutional breast MR examinations from the National Cancer Institute Cancer Imaging Archive, along with clinical, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
309
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(336 citation statements)
references
References 43 publications
14
309
1
12
Order By: Relevance
“…In recent years, applications of heterogeneity analysis have demonstrated the potential of MR imaging biomarkers in improving the specificity of breast MR and providing clinically relevant biological indicators of invasive breast cancers (2228). Until now, heterogeneity analysis has not been utilized in the development of MR imaging biomarkers of DCIS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, applications of heterogeneity analysis have demonstrated the potential of MR imaging biomarkers in improving the specificity of breast MR and providing clinically relevant biological indicators of invasive breast cancers (2228). Until now, heterogeneity analysis has not been utilized in the development of MR imaging biomarkers of DCIS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies utilizing heterogeneity analysis in the development of MR imaging biomarkers focused on differentiating benign from malignant breast lesions and molecular subtypes of invasive breast cancer (2224). Recent applications of heterogeneity analysis show promising results in the assessment of response of invasive breast cancer being treated with neoadjuvant therapy and the recurrence risk of invasive breast cancer (2528). …”
Section: Introductionmentioning
confidence: 99%
“…By converting medical images into highdimensional, mineable, and quantitative imaging features via high-throughput extraction of data-characterization algorithms, radiomics methods provide an unprecedented opportunity to improve decision-support in oncology at low cost and noninvasively (14,17). Some previous studies have shown that biomarkers based on quantitative radiomics features are associated with clinical prognosis and underlying genomic patterns across a range of cancer types (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reported promising performance of texture features and radiomics with and without the use of machine learning in the prediction of tumor response from MR mammography (MRM). Most MRM radiomics studies so far have focused specifically on contrast‐enhanced MR sequences, and have evaluated tumor response to neoadjuvant chemotherapy or prediction of histological subtype, OncotypeDX risk categories, early metastasis, molecular subtypes, gene and protein expression, and commonly used gene assays …”
mentioning
confidence: 99%